Good Company - Sweeney, Cynthia DAprix (New York, NY : Ecco, an imprint of HarperCollinsPublishers, 2021)
"In this follow-up to The Nest, Flora Mancini finds an envelope containing the wedding ring her husband, Julian, supposedly lost way back. Theyve been together 20 years, first as struggling actors in NYC barely managing to raise daughter Ruby and sustain Julians little acting company, then with bigger success on the West Coast. Does Julians duplicity mean their life together was a lie?"
Keywords: Marriage -- Fiction; Married people -- Fiction; Actors -- Fiction; Friendship -- Fiction; Deception -- Fiction; Adultery -- Fiction; Domestic fiction